The Influence of Ozone: Superstoichiometric Oxygen in Atomic Layer Deposition of Fe2O3 Using tert‐Butylferrocene and O3. Issue 11 (26th April 2020) - Schneider, Joel R.; Baker, Jon G.; Bent, Stacey F.
Abstract: Understanding the chemical mechanisms at play in atomic layer deposition (ALD) is critical for effective process development and expansion of ALD into more complex classes of materials. In this work, a mechanistic study of iron oxide deposited by ALD using tert ‐butylferrocene and ozone as reactants is performed. Iron oxide ALD using ozone is a useful model system for mechanistic studies due to the prevalence of ozone‐based ALD processes and the uses of iron oxide in ternary and quaternary metal oxides. Results show that saturation conditions require significantly greater exposures of both reactants than is typically reported in the literature, and growths per cycle of greater than one monolayer of Fe2 O3 per cycle are observed and explained. A growth mechanism is proposed whereby increased ozone exposure results in uptake of superstoichiometric oxygen into the film. X‐ray characterizations reveal the presence of excess oxygen stored near the surface of films deposited with larger ozone exposures and show that increased ozone exposures cause crystalline domain rearrangement and conversion of the film from the γ‐maghemite phase to the α‐hematite phase. The mechanism described here has implications for the wider class of ozone‐based ALD processes, and potential applications of this growth phenomenon are discussed. Abstract : This work demonstrates a mechanistic study of iron oxide deposited by atomic layer deposition (ALD), revealing a growth mechanism involving uptake of superstoichiometric oxygen. Material characterization shows ozone exposure can be used to convert the crystallographic phase and domain orientation of the materials. This mechanism has implications for wider classes of ozone‐based ALD processes and can generalize to other systems.